On the singular numbers for some integral operators - Meskhi, A. (Revista Matemática Complutense, 2001)
Two–sided estimates of Schatten–von Neumann norms for weighted Volterra integral operators are established. Analogous problems for some potential-type operators defined on Rn are solved.